How reliable is the next generation of multiplex-PCR for diagnosing prosthetic joint infection compared to the MSIS criteria? Still missing the ideal test. (September 2020) - Lausmann, Christian; Kolle, Kim Niklas; Citak, Mustafa; Abdelaziz, Hussein; Schulmeyer, Juan; Delgado, Gio D; Gehrke, Thorsten; Gebauer, Matthias; Zahar, Akos
Introduction: Identification of the pathogen in case of a periprosthetic joint infection (PJI) remains 1 of the greatest challenges in septic surgery. Rapid germ identification enables timely, specific, antimicrobial therapy. The first multiplex PCR (polymerase chain reaction) generation (Unyvero-i60) enables germ detection within 5 hours with a sensitivity of 78.8% and a specificity of 100%. The aim of this study is to investigate the performance of the new generation of cartridges (Unyvero-ITI) of multiplex PCR in the case of a PJI. Methods: In a prospective study, intraoperatively aspirated synovial fluid from 97 patients with aseptic or septic hip or knee revision surgery (49 aseptic, 48 septic) was examined with the multiplex PCR system (Unyvero-ITI) and the results were compared with the MSIS criteria. In addition, the time until the microbiological result was obtained in the event of a germ detection was documented. Results: The multiplex PCR showed a germ detection with a sensitivity of 85.1% and a specificity of 98.0%. In 7 cases a false negative result was found and in one patient a false positive result was found. The general accuracy of this test procedure was 91.8%. The detection of germs was carried out within 5 hours with the multiplex PCR compared to 4.9 days in conventional microbiological diagnostics. Conclusions: The new generation of multiplex-PCR was able to improve germ detection. The possibility of prompt detection of germs offers the option of faster, targeted antimicrobial therapy. This diagnostic tool offers significant advantages, particularly in the context of an acute periprosthetic infection.